Impact of a nurse-directed, coordinated school health program to enhance physical activity behaviors and reduce body mass index among minority children: A parallel-group, randomized control trial. - Wright, Kynna; Giger, Joyce Newman; Norris, Keth; Suro, Zulma (International Journal of Nursing Studies, 2013)
Background: Underserved children, particularly girls and those in urban communities, do not meet the recommended physical activity guidelines (>60 min of daily physical activity), and this behavior can lead to obesity. The school years are known to be a critical period in the life course for shaping attitudes and behaviors. Children look to schools for much of their access to physical activity. Thus, through the provision of appropriate physical activity programs, schools have the power to influence apt physical activity choices, especially for underserved children where disparities in obesity-related outcomes exist. Objectives: To evaluate the impact of a nurse directed, coordinated, culturally sensitive, school-based, family-centered lifestyle program on activity behaviors and body mass index. Design, settings and participants: This was a parallel group, randomized controlled trial utilizing a community-based participatory research approach, through a partnership with a University and 5 community schools. Participants included 251 children ages 8-12 from elementary schools in urban, low-income neighborhoods in Los Angeles, USA. Methods: The intervention included Kids N Fitness, a 6-week program which met weekly to provide 45 min of structured physical activity and a 45 min nutrition education class for parents and children. Intervention sites also participated in school-wide wellness activities, including health and counseling services, staff professional development in health promotion, parental education newsletters, and wellness policies for the provision of healthy foods at the school. The Child and Adolescent Trial for Cardiovascular Health School Physical Activity and Nutrition Student Questionnaire measured physical activity behavior, including: daily physical activity, participation in team sports, attending physical education class, and TV viewing/computer game playing. Anthropometric measures included height, weight, body mass index, resting blood pressure, and waist circumference. Measures were collected at baseline, completion of the intervention phase (4 months), and 12 months post-intervention. Results: Significant results for students in the intervention, included for boys decreases in TV viewing; and girls increases in daily physical activity, physical education class attendance, and decreases in body mass index z-scores from baseline to the 12 month follow-up. Conclusions: Our study shows the value of utilizing nurses to implement a culturally sensitive, coordinated, intervention to decrease disparities in activity and TV viewing among underserved girls and boys.